Response of MDA-MB231 cells to cisplatin and paclitaxel — viability, migration and gene expression estimation in mono- and co-culture with macrophages - Brygida Rusiecka; Oliwia Piwocka; Agnieszka Knopik-Skrocka (Reports of Practical Oncology and Radiotherapy)
BACKGROUND: Triple-negative breast cancer (TNBC) shows a high aggressiveness and chemoresistance. It is important to understand the biology of TNBC, including the influence of immune cells, such as macrophages, on cancer cells (CCs) and their response to chemotherapeutics. The research aimed to determine the effect of cisplatin (CisPt) and paclitaxel (PTX) on the viability, migratory ability and expression of selected genes of TNBC cells co-cultured with macrophages. The influence of macrophages alone on CCs was also studied. MATERIALS AND METHODS: The experiments were conducted with TNBC cell line (MDA-MB 231) and macrophages (THP1) in four experimental setups: MDA-MB231; MDA-MB231 + THP1; MDA-MB231 + CisPt or PTX; MDA-MB231 + THP1 + CisPt or PTX, using cytotoxicity and wound healing (WH) assays, flow cytometry and quantitative polymerase chain reaction (qPCR). RESULTS: Under PTX action, but not CisPt, a significant decrease in the number of MDA-MB 231 cells and their migration ability was observed. The presence of THP1 cells increases the survival of MDA-MB231 cells treated with CisPt, not PTX. A heatmap with the gene expression level has revealed that under THP1 CCs treated with PTX increase CDH2, GLUT-1 and LDHA expression. CONCLUSION: PTX is more toxic against MDA-MB231 cells than CisPt. M2 macrophages play an important role in MDA-MB231 cells gene expression, inducing changes in their metabolism and phenotype.